2017
DOI: 10.1080/1360080x.2017.1377961
|View full text |Cite
|
Sign up to set email alerts
|

Representation and conflict of interest among students on higher education governing boards

Abstract: An online survey administered to student trustees serving on governing boards drew 76 responses from 29 states and the District of Columbia. The results revealed that the students' views and positions were most influenced by other student leaders and least influenced by other board members, without significant difference by the respondents' race or gender. They also reported more influence from student leaders than from administrators. The students who were appointed by the state governor were much less likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, some newer studies have focused on the institutions' interactions with students. For example, Lozano and Hughes (2017) use PAT to study how student representatives in governing boards act on behalf of the student body's interests. Similarly, Dill and Soo (2004) argue that this theory helps to represent inefficiencies in how students select institutions and courses.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…However, some newer studies have focused on the institutions' interactions with students. For example, Lozano and Hughes (2017) use PAT to study how student representatives in governing boards act on behalf of the student body's interests. Similarly, Dill and Soo (2004) argue that this theory helps to represent inefficiencies in how students select institutions and courses.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…However, some have focused on the institution's interactions with students. For example, Lozano & Hughes (2017) used PAT to study how student representatives in governing boards act on behalf of the student body's interests. The authors explored whether the representatives truly represented their constituents versus their individual interests when voting on issues and found that students that were elected rather than appointed reported having more pressure from the student peers when it came to voting on issues.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For instance, early examples of student government and class councils were created to mirror the U.S. political system (May, 2010). Much like the political system, student governments have multiple branches of governance (May, 2010), vote on contentious initiatives and university matters (Goodman, 2022b;Goodman et al, 2021;Terrell & Cuyjet, 1994), and even have a seat on university boards of trustees (Lozano & Hughes, 2017;Templeton et al, 2018). To guide this study, we enlisted the following research questions:…”
Section: Discussionmentioning
confidence: 99%